Peran Tokoh Masyarakat dalam Penanaman Karakter Religius pada Remaja di Lingkungan Masyarakat Kelurahan Rajabasa, Kecamatan Rajabasa Kota Bandarlampung - Ratri Hening Pahayu (University of Lampung, 2020)
Teenagers as the next generation of a nation are believed to be able to embody the idea of homeland by mastering the power religious spiritual, self control, smartness, noble attitude, along with skill which are necessary for themselves, community and nation. Multidimensional in term of moral decadency is now found among teenagers, the succesors of nation’s hope. Moral decadency of teenagers is marked by some indicators related to some phenomena such as, smoking, alcohol addicted and sex pre marriage which are now escalating and easily found in community environment. Religion is a solid shield to prevent moral decadency. Religion norm is imparative to guide and to lead teenagers behavior in accordance with moral standard applied in community is supposed to be done by those who own important influence such as local community public figures.The research was aimed to describe and analyze the role of local public figures in cultivating religious character to local teenagers. Research method applied was quantitative descriptive. Research subject were teenegers in community environment in Rajabasa Urban Village.. Sample of the research were 45 respondens. Data was analyzed by using product moment formula to calculate the correlation between the two variables, then followed by a regression analysis in order to determine its significance. The value rxy= 0,78, which meant sufficient category. The result of regression analysis between variable X and variable Y obtained Fcount Ftable or 67,8 4,20. Ho was rejected and Ha was accepted. This justifies meaning that the increasing role of community leaders will increase the inculcation of religious character in teenegers, so that this becomes an impetus for local community public figures to increase their exemplary attitude, habituation, advice / attention and sanctions by providing good role models. Keywords: Public Figures, Religious Character, Teenagers